GAME POWER POINT BASED SETELA MEDIA DEVELOPMENT FOR FOURTH-GRADE ELEMENTARY SCHOOL TO MASTER CIVICS MATERIALS - Novita Cindy Nuriyanto; Arief Cahyo Utomo (Universitas Majalengka, 2023)
The lack of students’ understanding of the basis of the state, namely Pancasila, is the main point of this research. Add more with the teacher’s limitations in utilizing learning media that makes students get bored easily. The research objective was to produce SETELA Power Point-based learning and test the feasibility of media when applied to Civics learning in Pancasila material theme 5 of fourth-grade. This study uses the Research and Development (R&D) method with ADDIE model which consists of analysis, design, development, implementation, and evaluation stages. The sample used 16 students of fourth-grade MIM Karanglo. A questionnaire data collection technique was employed for the descriptive qualitative data analysis, and validators included media and subject matter experts, classroom teachers, and fourth-grade children. With a proportion of 81.9% and 95.3%, validation by media experts and material experts very valid criteria. When the media used in schools, it results in class instructors and 16 fourth-grade students’ approval with extremely good criteria with a percentage of 88.6% and 95.3%. The whole validation yields an average percentage of 89.4% with very good criteria. It can be said that SETELA learning materials are suitable for teaching civics in fourth-grade primary school Pancasila theme content. Because it contains brief, understandable content and offers engaging games even with basic media, particularly Power Point, the implications of this media in the future can be a teacher’s tool in using interactive instructional media to deepen Pancasila material for fourth-grade elementary school students. Kurangnya pemahaman siswa akan dasar negara yakni pancasila menjadi poin utama penelitian ini. Ditambah dengan keterbatasan guru dalam memanfaatkan media pembelajaran menjadikan siswa lebih cepat bosan. Tujuan penelitian adalah menghasilkan media pembelajaran SETELA berbasis Power Point dan menguji kelayakan media saat diterapkan pada pembelajaran PPKn dalam materi pancasila tema 5 kelas 4 SD. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang terdiri dari tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Sampel yang digunakan adalah 16 siswa kelas 4 MIM Karanglo. Analisis data yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data angket atau kuisioner yang terdiri dari instrumen pengumpulan validasi yang berasal dari validator (ahli media dan ahli materi), guru kelas, dan siswa kelas 4. Validasi dari ahli media dan ahli materi menunjukkan kriteria sangat valid dengan presentase 81,9% dan 95.3%. Saat media diterapkan di sekolah dihasilkan validasi dari guru kelas dan 16 siswa kelas 4 dengan kriteria sangat baik yakni dengan presentase 88,6% dan 91.7%. Adapun hasil rata-rata validasi keseluruhan menghasilkan presentase 89,4% dengan kriteria sangat valid. Dapat disimpulkan bahwa media pembelajaran SETELA layak digunakan dalam pembelajaran PPKn kelas 4 SD tema 5 materi pancasila. Implikasi media ini kedepannya dapat menjadi alat bantu guru dalam pemanfaatan media pembelajaran interaktif untuk pendalaman materi pancasila siswa kelas 4 SD karena dilengkapi dengan materi yang ringkas dan jelas serta dengan penyajian permainan yang menarik walaupun dengan media sederhana khususnya power point.